OARSI Clinical Trials Recommendations: Hand imaging in clinical trials in osteoarthritis - Hunter, D. J.; Arden, N.; Cicuttini, Flavia M.; Crema, M. D.; Dardzinski, B.; Duryea, J.; Guermazi, Ali; Haugen, I. K.; Kloppenburg, M.; Maheu, E.; Miller, C. G.; Martel-Pelletier, J.; et al. (Osteoarthritis and Cartilage, 2015)
Tremendous advances have occurred in our understanding of the pathogenesis of hand osteoarthritis (OA) and these are beginning to be applied to trials targeted at modification of the disease course. The purpose of this expert opinion, consensus driven exercise is to provide detail on how one might use and apply hand imaging assessments in disease modifying clinical trials. It includes information on acquisition methods/techniques (including guidance on positioning for radiography, sequence/protocol recommendations/hardware for MRI); commonly encountered problems (including positioning, hardware and coil failures, sequences artifacts); quality assurance/control procedures; measurement methods; measurement performance (reliability, responsiveness, validity); recommendations for trials; and research recommendations.
EVALuna2:14529